Innovations in the English Classroom: The Students' Perceptions Toward Robot Media - Yuliani, Sri; Hartanto, Dicki; Linarta, Arie (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This study sought to pinpoint key requirements for incorporating technology into education. A survey of junior high schools was used in the study which took a qualitative approach. A research sample of 35 students who were chosen purposively for the study were given the questionnaire as a data gathering tool with three components; the utility/feature of usage, the interest, and the pedagogical content of the Evoce robot. The data was analyzed by using the Guttman scale has a CS of at least 0.60 and a CR of at least 0.90, it was considered to meet the unidimental and cumulative features. The findings showed the mean of CR from three indicators was 0.908, which means the result of CR was valid while the mean score was CS was 0.798, which means that the coefficients of scalability were considered good. Based on the result findings students' opinions about the usage of the Evoce robot as technology in the learning process were inversely correlated with their usage of learning media was helping them in attaining new media of teaching was the Evoce robot. It recommended that robots might give an alternative interesting media in class, especially for teaching vocabulary.